Soil loss by water erosion in areas under maize and jack beans intercropped and monocultures - Lima,Pedro Luiz Terra (2014)
Adequate soil management can create favorable conditions to reduce erosion and water runoff, consequently increase water soil recharge. Among management systems intercropping is highly used, especially for medium and small farmers. It is a system where two or more crops with different architectures and vegetative cycles are explored simultaneously at the same location. This research investigated the effects of maize intercropped with jack bean on soil losses due to water erosion, estimate C factor of Universal Soil Losses Equation (USLE) and how it can be affected by soil coverage. The results obtained also contribute to database generation, important to model and estimate soil erosion. Total soil loss by erosion caused by natural rain, at Lavras, Minas Gerais, Brazil, were: 4.20, 1.86, 1.38 and 1.14 Mg ha-1, respectively, for bare soil, maize, jack bean and the intercropping of both species, during evaluated period. Values of C factor of USLE were: 0.039, 0.054 and 0.077 Mg ha Mg-1 ha-1 for maize, jack bean and intercropping between both crops, respectively. Maize presented lower vegetation cover index, followed by jack beans and consortium of the studied species. Intercropping between species showed greater potential on soil erosion control, since its cultivation resulted in lower soil losses than single crops cultivation, and this aspect is really important for small and medium farmers in the studied region.